CARYOCHROITE, A NEW HETEROPHYLLOSILICATE MINERAL SPECIES RELATED TO NAFERTISITE, FROM THE LOVOZERO MASSIF, KOLA PENINSULA, RUSSIA - Kartashov P.M.; Soboleva S.V.; Ferraris G.; Chukanov N.V. (My University, 2006)
Caryochroite, a new mineral species, ideally (Na,Sr) 3 (Fe 3+ ,Mg) 10 [Ti 2 Si 12 O 37 ](H 2 O,O,OH) 17 , is monoclinic, with cell param-eters a 16.47, b 5.303, c 24.39 Å, 93.5°, Z = 2. It was collected on the dumps of the Umbozero mine, Mount Alluaiv, Lovozero massif, Kola Peninsula, Russia. It is associated with albite, elpidite, epididymite, quartz, natrolite, pyrite, galena, sphalerite and bitumen. Caryochroite is the product of the supergene alteration of an unidentifi ed Fe 2+ -rich protophase; it forms centimetric crusts. Physical properties: submicrometric {001} lamellae, [010] elongate; opaque; hazel-brown color; pale brownish yellow streak; dull to waxy luster; hardness, 2½; good {001} cleavage; D meas 2.990 g cm –3 ; biaxial (–), <1.700, 1.745, 1.775, 2V meas 75°; pleochroism: X = Y (dark brown) > Z (brown). The name refers to the color. Chemical data from electron microprobe, wet-chemical analysis for Fe and thermal analysis (9.17 wt% loss at 800°C); Mössbauer spectroscopy shows major Fe 3+ and minor Fe 2+ ; the empirical formula is (Na 1.19 Sr 0.62 Ca 0.41 Mn 0.35 K 0.26) 2.83 (Fe 3+ 7.98 Mg 1.15 Mn 0.49 Fe 2+ 0.38) 10.00 (Ti 1.87 Fe 3+ 0.13) 2.00 (Si 11.74 Al 0.26) 12.00 O 54.10 H 20.40 . The spacing (Å) and intensity (%) of the strongest six lines of the X-ray powder-diffraction pattern are: 14.1(20), 13.3(30), 12.1(100), 4.38(10), 2.692(12), and 2.631(13). The cell parameters, X-ray powder-diffraction pattern, chemical composition and infrared spectrum suggest that caryochroite is the second heterophyllosilicate based on a nafertisite-type HOH layer. We evaluate the role of caryochroite and associated titano-and zirconosilicates as catalysts of the in situ formation of bitumen.
Keywords: Caryochroite